Moderasi Islam dalam Dimensi Berbangsa, Bernegara Dan Beragama Perspektif Maqashid Asy-Syari'ah - M. Luthfi Afif Al Azhari (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2020)
(Wasaṭiyyah is attached to Islam since he was born and will continue to cling to the Day of Judgment. In its history, after the division in the body of Muslims which gave birth to many schools and schools, the nature of Wasaṭiyyah was attached to the Ahlus Sunnah wa al-jama'ah-leaning group, including the theology of Ash'ariyah and Maturidiyah. Maqashid shari'ah arises due to debate among fiqh experts about shari'ah, which has a certain 'illat (causa) or not. The debate has led to various kinds of flow including the ulama 'ushul fiqh. Maqhasid al-ahkam is considered as the basis in establishing a law, and can be categorized as the main foundation in law. As information about al-kulliyyat al-khams and their limitations, ḥifzh ad-din (protection of religion), ḥifzh an-nafs (protection of life), ḥifzh al-'aql (intellectual protection), ḥifzh an-nasl (genetic protection), and ḥifzh al-māl (protection of property). (Wasaṭiyyah melekat pada islam semenjak ia lahir dan akan terus melekat sampai hari kiamat nanti. Dalam sejarahnya, pasca terjadinya perpecahan dalam tubuh umat islam yang melahirkan banyak madzhab dan aliran, sifat Wasaṭiyyah melekat pada golongan yang berhaluan Ahlus Sunnah wa al-jama'ah, termasuk didalamnya aliran teologi Asy'ariyah dan Maturidiyah. Maqashid syari'ah muncul akibat perdebatan di antara pakar fiqh mengenai syari'ah, yang memiliki 'illat (kausa) tertentu ataukah tidak. Perdebatan tersebut menimbulkan berbagai macam aliran tak terkecuali di kalangan ulama' ushul fiqh. Maqhasid al-ahkam dianggap sebagai dasar dalam penetapan suatu hukum, dan dapat dikategorikan sebagai landasan utama dalam hukum. Sebagaimana keterangan mengenai al-kulliyyat al-khams beserta batasannya, ḥifzh ad-din (perlindungan agama), ḥifzh an-nafs (perlindungan jiwa), ḥifzh al-'aql (perlindungan intelektual), ḥifzh an-nasl (perlindungan genetik), dan ḥifzh al-māl (perlindungan harta).